2017
DOI: 10.1007/s00264-017-3707-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and the associated cutoff values for failure of corticosteroid injection in treatment of Morton’s neuroma

Abstract: This study found that, with a cut-off value of 6.3 mm, larger Morton's neuromas were associated with failure of corticosteroid injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…The results of this study suggest that the size of the neuroma is the sole predictor of failure of corticosteroid injections for the treatment of Morton neuroma. This finding is consistent with the results of previous publications . Intermetatarsal distance, another ultrasonographic parameter, did not predict the clinical prognosis of Morton neuroma.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study suggest that the size of the neuroma is the sole predictor of failure of corticosteroid injections for the treatment of Morton neuroma. This finding is consistent with the results of previous publications . Intermetatarsal distance, another ultrasonographic parameter, did not predict the clinical prognosis of Morton neuroma.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the results of previous publications. [10][11][12] Intermetatarsal distance, another ultrasonographic parameter, did not predict the clinical prognosis of Morton neuroma. This result is similar to the results of studies examining radiographic evaluations of foot morphology in patients with Morton neuroma.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Real‐time assessment is another advantage of sonography and enables treatment of Morton neuromas by nonoperative injection of local anesthetic agents, alcohol, and corticosteroids into the affected space . In many cases, these treatments are performed under ultrasound guidance, which improves accuracy of the diagnosis.…”
mentioning
confidence: 99%
“…In previous studies, many authors indicated that the size of the neuroma is strongly associated with symptom development and prognosis . In addition, a recent study indicated that the size of the neuroma was a risk factor for failure of corticosteroid injection and that the cutoff value was 6.3 mm . However, although many authors have emphasized the importance of neuroma size, no studies have investigated the reliability of sonographic measurement of the size of the neuroma.…”
mentioning
confidence: 99%